2003
DOI: 10.1258/002367703322389889
|View full text |Cite
|
Sign up to set email alerts
|

Are the effects of different enrichment designs on the physiology and behaviour of DBA/2 mice consistent?

Abstract: SummaryEnvironmental enrichment is intended to improve the well-being of laboratory animals. Although many researchers have indicated that environmental enrichment may enhance animal well-being, there is some evidence that enrichment differs in its effects on physiology and behaviour between species and strains. The present study focuses on the effects of different enrichment designs on the physiology and behaviour of male and female DBA=2 mice. A total of 48 DBA=2J mice, 24 males and 24 females were used for … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
47
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 27 publications
3
47
1
Order By: Relevance
“…In studies where enriched animals received toys and nesting material as enrichment, the locomotor counts of female B6 mice in the open field were lower for the enriched groups (Dahlborn 1996;Yee et al 2007). Locomotor activity was also lower in D2 female mice which received enrichment consisting of a shelter and a climbing toy, but increased when the enrichment consisted of vertical and horizontal dividers (Tsai et al 2003). Performance of both B6 (a different substrain) and D2 mice in a food seeking task was shown to be improved by exposure to an enriched environment (Henderson 1976).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In studies where enriched animals received toys and nesting material as enrichment, the locomotor counts of female B6 mice in the open field were lower for the enriched groups (Dahlborn 1996;Yee et al 2007). Locomotor activity was also lower in D2 female mice which received enrichment consisting of a shelter and a climbing toy, but increased when the enrichment consisted of vertical and horizontal dividers (Tsai et al 2003). Performance of both B6 (a different substrain) and D2 mice in a food seeking task was shown to be improved by exposure to an enriched environment (Henderson 1976).…”
Section: Discussionmentioning
confidence: 98%
“…Broadly, environmental enrichment incorporates both inanimate and social factors which promote enhanced sensory, cognitive and motor stimulation (Rosenzweig andBennett 1996, Mohammed et al 2002;Olsson and Dahlborn 2002;. The effects of physical enrichment on behavioral data variation have been inconstant when applying different enrichment designs (Tsai et al 2003). However, other authors showed that, for female mice, environmental enrichment, in the form of more space, additional resources, increased complexity, and novelty, has a consistent effect on behavioral variables across laboratories and does not increase the proportion of Strain*laboratory variance (Wolfer et al 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The results show clear differences between rats experiencing complex and novel housing also been demonstrated to denote good welfare in laboratory rats (Manser, 1992;Blanchard et al, 1995;Haller et al, 1998;Tsai et al, 2003;Živkovic et al, 2005). Similarly, aggression, non-aggressive social interaction, awake non-active behaviours, away from enrichment, underneath hopper and audible vocalizations have been used to judge the welfare of laboratory rodents with elevated levels being indicative of a generally compromised welfare state (Adams, 1977;Vivian and Miczek, 1993;Marashi et al, 2004; see also Fureix and Meagher 2016).…”
Section: Discussionmentioning
confidence: 66%
“…(ILAR 1996, 52) Some scientists have raised concerns that environmental enrichment may compromise experimental standardization by introducing variability, adding not only diversity to the animals' behavioral repertoire but also variation to their responses to experimental treatments (e.g., Eskola et al 1999;Gärtner 1999;Tsai et al 2003;Bayne 2005). (ILAR 1996, 54) Since it is critical that experimental outcomes are accurate and reproducible, it is important that the data obtained from rodents correctly represent the actual (average) response(s) to whatever perturbation is under investigation.…”
Section: Introductionmentioning
confidence: 99%